Social Forestry Extension in West Bengal a Decade in Retrospect - Bardhan Roy, B. K. (Indian Forester, 1991)
The West Bengal Social Forestry Project was launched for a period of six years from 1981 to 1987 and later extended upto 31.3.1991. A decade In retrospect of the project is described In this paper.